2001
DOI: 10.1159/000049685
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Big-Endothelin Concentrations Are Elevated in Liver Graft Tissue during Cold Storage and Reperfusion

Abstract: Endothelin (ET) and its precursor big-ET were synchronously analyzed by RIA in liver biopsies and systemic plasma during porcine orthotopic liver transplantation (OLT) before graft harvesting (phase A), after cold storage (phase B), and early (phase C) and late reperfusion (phase D). Tissue and plasma concentrations were correlated with length of survival and reperfusion. Increased tissue ET/big-ET levels were already detected during phase B (ET: 46 ± 20; big-ET: 245 ± 119 pg/mg cytosolic protein) and remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Because a significant improvement of OCR and bile production was observed only after 60 min or later (data not shown), the primary action of hydrogen gas was apparently to induce vascular relaxation. In their study, the tissue ET-1 level significantly decreased at 90 min after reperfusion in surviving animals, whereas it remained at a high value in non-survivors (28). 4).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because a significant improvement of OCR and bile production was observed only after 60 min or later (data not shown), the primary action of hydrogen gas was apparently to induce vascular relaxation. In their study, the tissue ET-1 level significantly decreased at 90 min after reperfusion in surviving animals, whereas it remained at a high value in non-survivors (28). 4).…”
Section: Discussionmentioning
confidence: 84%
“…Kraus et al reported that the tissue endothelin-1 level was already augmented during cold preservation and after 5 min of reperfusion in a pig liver transplant model. In their study, the tissue ET-1 level significantly decreased at 90 min after reperfusion in surviving animals, whereas it remained at a high value in non-survivors (28). Tissue blood flow was significantly lower than that of survivors from 5 min to 3 h after reperfusion in the warm hepatic I/R model (8).…”
Section: Discussionmentioning
confidence: 87%